Measuring Business Interruption Losses and Other Commercial Damages, 3rd Edition - Gaughan, Patrick (Wiley, 2020)
Measure business interruption losses with confidence You hope for the best and plan for the worst. It's your job. But when the unimaginable happens, are you truly prepared for those business interruption losses? Measuring Business Interruption Losses and Other Commercial Damages is the only book in the field that explains the complicated process of measuring business interruption damages after you've been hit by the unexpected, whether the losses are from natural or man-made disasters, or whether the performance of one company adversely affects the performance of another. Understand the methodology for how lost profits should be measured Deal with the many common types of cases in business interruption lawsuits in commercial litigation Take a look at exhibits, tables, and graphs Benefit from updated data, case studies, and case law references Don't get caught off guard. Get ahead of planning for measuring your interruption losses before disaster strikes.